2003
DOI: 10.3141/1852-31
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Queue Modeling for On-Ramp–Freeway Junctions

Abstract: With reference to the procedure in the Highway Capacity Manual (HCM) 2000 for estimation of measures of effectiveness, a model is proposed to estimate merge-area capacity and to predict traffic dynamics and queue evolution for on-ramp–freeway junctions. The aims of the study are to analyze the behavior of flows within the merge area and to propose a methodology to dynamically estimate the capacity of both ramp and main line according to inflow patterns and to develop a mesoscopic model of merge facilities that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The most widely used method of calculating the capacity of freeway merge areas has been known as the gap-acceptance model [6][7][8][9]. Previous researchers have suggested that gap-acceptance models cannot only provide a scientific approach to studying traffic control maneuvers [10,11], but they can also calculate vehicle queue length on the ramp [12,13] and the service quality of the freeway merge areas [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used method of calculating the capacity of freeway merge areas has been known as the gap-acceptance model [6][7][8][9]. Previous researchers have suggested that gap-acceptance models cannot only provide a scientific approach to studying traffic control maneuvers [10,11], but they can also calculate vehicle queue length on the ramp [12,13] and the service quality of the freeway merge areas [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Few efforts, however, were found to specifically analyze merge-area capacity or breakdown. Albanese et al established a dynamic model to estimate capacity of both the ramp and the mainline on the basis of gap-acceptance theories (8). The model used variables such as α (mainline priority) and β (minor-road priority), which need to be calibrated with field data.…”
mentioning
confidence: 99%